2020
DOI: 10.1128/jb.00654-19
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Methylation of Arginine in Methyl Coenzyme M Reductase Has a Profound Impact on both Methanogenesis and Growth of Methanococcus maripaludis

Abstract: Catalyzing the key step for anaerobic production and/or oxidation of methane and likely other short-chain alkanes, methyl coenzyme M reductase (Mcr) and its homologs play a key role in the global carbon cycle. The McrA subunit possesses up to five conserved posttranslational modifications (PTMs) at its active site. It was previously suggested that methanogenesis marker protein 10 (Mmp10) could play an important role in methanogenesis. To systematically examine its physiological role, mmpX (locus tag MMP1554), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…A unique radical SAM methyltransferase was shown required for methylation of the active-site arginine and concluded important for stability under imposed oxidative and heat stress (Deobald et al, 2018;Radle et al, 2019). Deletion of a homolog essential for arginine methylation in the obligate CO 2 -reducing methanogen Methanococcus maripaludis resulted in a 40-60% loss in the rate of methanogenesis consistent with partial loss of Mcr activity (Lyu et al, 2020). Deletion of two genes essential for thioglycine synthesis in McrA of Ms. acetivorans produced mutants severely impaired in the rate of growth with acetate and when exposed to thermal and oxidative stress, results supporting a role for thioglycine in stabilizing the McrA active-site although not essential.…”
Section: One-carbon Reactionsmentioning
confidence: 97%
“…A unique radical SAM methyltransferase was shown required for methylation of the active-site arginine and concluded important for stability under imposed oxidative and heat stress (Deobald et al, 2018;Radle et al, 2019). Deletion of a homolog essential for arginine methylation in the obligate CO 2 -reducing methanogen Methanococcus maripaludis resulted in a 40-60% loss in the rate of methanogenesis consistent with partial loss of Mcr activity (Lyu et al, 2020). Deletion of two genes essential for thioglycine synthesis in McrA of Ms. acetivorans produced mutants severely impaired in the rate of growth with acetate and when exposed to thermal and oxidative stress, results supporting a role for thioglycine in stabilizing the McrA active-site although not essential.…”
Section: One-carbon Reactionsmentioning
confidence: 97%
“…The core modified amino acids are widely conserved and include N 1 -methylhistidine (or 3-methylhistidine), 5-(S)-methylarginine, and thioglycine ( Fig 1B). The widespread conservation of these core modifications is exemplified by the recently discovered enzymes responsible for installation of the thioglycine and 5-(S)-methylarginine modifications, whose encoding genes were originally designated as methanogenesis marker genes because of their universal occurrence in the genomes of sequenced methanogens [26][27][28][29][30]. Given that 5-(S)methylarginine and thioglycine are extremely rare in nature, yet universally conserved in MCR, it was speculated that these residues must be essential for catalysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…This study was the first to link MCR activity and a specific PTM. It also firstly demonstrates that a PTM could affect both methanogenesis and cell growth without the addition of stressor ( Lyu et al, 2020 ). Furthermore, this study also indicated a high specificity of Mmp10 to McrA and the binding sites of cofactors, SAM, and cobalamin, in Mmp10 ( Lyu et al, 2020 ).…”
Section: Post-translational Modifications Of Mcrsmentioning
confidence: 97%
“…It also firstly demonstrates that a PTM could affect both methanogenesis and cell growth without the addition of stressor ( Lyu et al, 2020 ). Furthermore, this study also indicated a high specificity of Mmp10 to McrA and the binding sites of cofactors, SAM, and cobalamin, in Mmp10 ( Lyu et al, 2020 ). For glutamine methylation, although the putative cobalamin-dependent radical SAM enzyme has been proposed ( Deobald et al, 2018 ), there has been no solid evidence.…”
Section: Post-translational Modifications Of Mcrsmentioning
confidence: 97%
See 1 more Smart Citation